Investigation of Diurnal Variation of Signal Strength Generated by FM Transmitter - Iwuji, Prince Chigozie; Onuabuchi, Victor Chukwuagozie (European Scientific Journal, ESJ, 2018)
This paper focuses on the determination of the diurnal variation of signal strength generated by Orient 94.4 FM transmitter along six (6) selected route in Imo State, Nigeria. This was carried out with the aid of a constructed signal strength meter (SSM). Signal strength measurements were collected at different time, on different days, and in different months. The measurement was carried out at a constant distance of 20 Km. Arrangement was made with the management of the base station to ensure that the transmitting parameters were kept constant throughout the period of signal strength measurement. The average results of these measurements were taken. The data obtained from the measurements was plotted in a graph to establish the diurnal variation in signal strength along the different routes of signal strength measurement. It was observed from this research that transmission and reception of signals are dependent on the time of the day. High signal strength was noted between the hours of 8 am and 11 am, while low signal strength was recorded between the hours of 1 pm and 5 pm. Better signal strengths were recorded at night. The result of this study shows that signal strength generated by FM transmitter vary with time of the day and the prevalent weather conditions. Stronger signals are recorded mostly at night along the different routes of the study. The signal strength consequently drops in the afternoon and recovers in the morning hours.